Peptide ligand recognition by G protein-coupled receptors - Krumm, Brian E.; Grisshammer, Reinhard (Frontiers in Pharmacology, 2015)
The past few years have seen spectacular progress in the structure determination of G protein-coupled receptors (GPCRs). We now have structural representatives from classes A, B, C, and F. Within the rhodopsin-like class A, most structures belong to the α group, whereas fewer GPCR structures are available from the β, γ, and δ groups, which include peptide GPCRs such as the receptors for neurotensin (β group), opioids, chemokines (γ group), and protease-activated receptors (δ group). Structural information on peptide GPCRs is restricted to complexes with non-peptidic drug-like antagonists with the exception of the chemokine receptor CXCR4 that has been crystallized in the presence of a cyclic peptide antagonist. Notably, the neurotensin receptor (NTSR1) is to date the only peptide GPCR whose structure has been solved in the presence of a peptide agonist. Although limited in number, the current peptide GPCR structures reveal great diversity in shape and electrostatic properties of the ligand binding pockets, features that play key roles in the discrimination of ligands. Here, we review these aspects of peptide GPCRs in view of possible models for peptide agonist binding.